Reconstruction from breakdown in Northeastern India: Building state capability - M. Sajjad Hassan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The northeast region of India remains fraught with severe violence, poor growth and acute frustration among its youth. Success of policies to resolve the region's crisis has proved less than encouraging. What could be the way out of the violence–poor growth trap? This paper argues that a key determinant of the instability in the region is the absence of the effective role of the state: to provide security and opportunities for social and economic wellbeing equitably to all sections of society; and to uphold the rule of law. For reconstruction to work the state must act to provide key political goods to all its citizens, and restore its legitimate authority by implementing policies and enforcing laws cleanly and transparently. Political leaders can contribute to this endeavour by organizing politics inclusively. – conflict ; reconstruction ; state-building ; capability ; legitimacy ; rule of law ; governance ; institutions ; development ; growth ; cohesiveness ; inclusive politics
Keywords: R11; R58; O18; 330; Regionalökonomik; Regionalpolitik; Indien (Nordost)